Dopant‐Free Squaraine‐Based Polymeric Hole‐Transporting Materials with Comprehensive Passivation Effects for Efficient All‐Inorganic Perovskite Solar Cells. Issue 49 (22nd October 2019) - Xiao, Qi; Tian, Jingjing; Xue, Qifan; Wang, Jing; Xiong, Bijin; Han, Mengmeng; Li, Zhen; Zhu, Zonglong; Yip, Hin‐Lap; Li, Zhong'an
Abstract: Development of high‐performance dopant‐free hole‐transporting materials (HTMs) with comprehensive passivation effects is highly desirable for all‐inorganic perovskite solar cells (PVSCs). Squaraines (SQs) could be a candidate for dopant‐free HTMs as they are natural passivators for perovskites. One major limitation of SQs is their relatively low hole mobility. Herein we demonstrate that polymerizing SQs into pseudo two dimensional (2D) p–π conjugated polymers could overcome this problem. By rationally using N, N‐diarylanilinosquaraines as the comonomers, the resulting polysquaraine HTMs not only exhibit suitable energy levels and efficient passivation effects, but also achieve very high hole mobility close to 0.01 cm −2 V −1 s −1 . Thus as dopant‐free HTMs for α‐CsPbI2 Br‐based all‐inorganic PVSCs, the best PCE reached is 15.5 %, outperforming those of the doped‐Spiro‐OMeTAD (14.4 %) based control devices and among the best for all‐inorganic PVSCs. Abstract : Squaring the hole : Using N, N ‐diarylanilinosquaraines as the comonomers gives polysquaraine hole‐transporting materials (HTMs) that have very high hole mobility. As a dopant‐free HTM for α‐CsPbI2 Br‐based all‐inorganic perovskite solar cells, the power conversion efficiency (PCE) can reach 15.5 %, among the best for all‐inorganic PVSCs.